2000
DOI: 10.1152/ajprenal.2000.279.3.f440
|View full text |Cite
|
Sign up to set email alerts
|

A functional angiotensin II receptor-GFP fusion protein: evidence for agonist-dependent nuclear translocation

Abstract: We constructed an expression vector for a fusion protein [ANG II type 1a receptor-green fluorescent protein (AT(1a)R-GFP)] consisting of enhanced GFP attached to the COOH terminus of the rat AT(1a)R. Chinese hamster ovary (CHO) cells transfected with AT(1a)R-GFP demonstrated specific, high-affinity (125)I-labeled ANG II binding (IC(50) 21 nM). ANG II exposure stimulated sodium-proton exchange and cytoplasmic calcium release to a similar extent in cells transfected with AT(1a)R or AT(1a)R-GFP; these responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 32 publications
4
69
0
Order By: Relevance
“…nuclei of epithelial cells or isolated from the kidney, [97][98][99][100] there is no study specifically designed to localise internalised Ang II and AT 1 -receptors in proximal tubule cells in vitro and in vivo. It would be interesting to use state-of-the-art electron microscopic autoradiography and immunohistochemistry to localise internalised Ang II and AT 1 -receptors, focusing mainly in proximal tubule cells ex vivo, and use confocal and fluorescence microscopy for similar studies in cultured proximal tubule cells in vitro.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
See 2 more Smart Citations
“…nuclei of epithelial cells or isolated from the kidney, [97][98][99][100] there is no study specifically designed to localise internalised Ang II and AT 1 -receptors in proximal tubule cells in vitro and in vivo. It would be interesting to use state-of-the-art electron microscopic autoradiography and immunohistochemistry to localise internalised Ang II and AT 1 -receptors, focusing mainly in proximal tubule cells ex vivo, and use confocal and fluorescence microscopy for similar studies in cultured proximal tubule cells in vitro.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
“…Intracellular kinases activated by Ang II include extracellular signal-regulated protein kinase(s) (ERKs) 63,70,117,122 JAK-STAT signalling 117,123,124 and calcineurin phosphatase. 126,127 Internalised Ang II may also be translocated to the nucleus, 20,97,99,110 where it may activate nuclear calcium 28,29,45 and stimulate transcription of NHE-3 and pro-inflammatory cytokines and growth factors. 20,47,69,97,111,128 Recent studies indicate that Ang II activates nuclear transcription factor NF-κB and activator protein-1 (AP-1) in the kidney, leading to longlasting inflammatory and growth-promoting effects.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
See 1 more Smart Citation
“…7 These observations again raise the possibility that complete intracellular renin-angiotensin systems exist in some cells. [13][14][15][32][33][34][35][36] These intracrine renin-angiotensin systems (iRAS) could offer a new therapeutic target, given the differential ability of various inhibitors to act at intracellular sites. Parenthetically, regulatory loops linking the iRAS components angiotensinogen with p53 and renin with nucleolin mirror the regulatory relations of other intracrines with p53 and nucleolin.…”
Section: Intracrine Prorenin/reninmentioning
confidence: 99%
“…Moreover, electron microscopic immunohistochemical techniques were used to demonstrate angiotensin II immunoreactivity located in association with the euchromatin of cerebellar neurons, hepatocytes, and adrenal cells from normal animals (13). Also confocal microscopy studies demonstrated that functional fluorescent-labeled At-1 receptors traffic to the nuclear interior upon agonist binding (7). In addition, the direct introduction of angiotensin or renin into the intracellular space produced alterations in calcium flux and conductance in cardiac myocytes (11,14,47).…”
Section: Intracrine Renin Angiotensin Systemmentioning
confidence: 99%